A proposal for measuring hotels managerial responses to User-Generated-Content Reviews - Perez-Aranda,Javier (2018)
Despite the fact that User-Generated-Content (UGC) has emerged as a widely implemented practice in many disciplines and industries, including tourism and hospitality, academic research lacks a measurement method for hotels managerial responses to UGC- Reviews (UGC-R). Based on data from a survey of 335 hotels, this article validates a 32-item UGC-Review scale that, through a battery of exploratory factorial analysis tests, comprises 6 constructs: identification of the reputation landscape; assessment of changes in the company´s ratings and rankings over time; determination of the publication reach; comparison with industry competitors; review and comparison of ranking methodologies and increased reputational scores. The results show that the proposal scale demonstrates reliability and dimensionality. The proposed UGC-R scale is a strategic tool for business managers aiming to improve their marketing strategies and to gain insights into the competitive advantage of reputation management.